2022
DOI: 10.18026/cbayarsos.1081570
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Career Satisfaction and Work Engagement: A Research on Public Employees

Abstract: The aim of this research is to explain the relationship between career satisfaction and work engagement variables in the context of public employees. For this purpose, the Utrecht Work Engagement Scale and the Career Satisfaction Scale were applied to 334 employees employed in public institutions in Manisa. According to the findings obtained as a result of the analysis of the collected data, there is a positive correlation between career satisfaction and work engagement variable and all its sub-dimensions (vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is thought that the increase in professional experience is effective in forming this significant differentiation. On the other hand, there are studies in the literature that found that work engagement does not differ according to age variable (Asmadili, 2020;Atalık, 2021;Bostancı & Ekiyor, 2015;Güneş, 2022;Turgut, 2011). In the study, the work engagement levels of teachers with postgraduate education were found to be higher than those of teachers with undergraduate degrees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that the increase in professional experience is effective in forming this significant differentiation. On the other hand, there are studies in the literature that found that work engagement does not differ according to age variable (Asmadili, 2020;Atalık, 2021;Bostancı & Ekiyor, 2015;Güneş, 2022;Turgut, 2011). In the study, the work engagement levels of teachers with postgraduate education were found to be higher than those of teachers with undergraduate degrees.…”
Section: Discussionmentioning
confidence: 99%
“…When the related literature is reviewed, job commitment levels differ significantly according to seniority (Atalık, 2021). On the other hand, there are also research results where work engagement levels do not differ significantly according to teachers' seniority (Güneş, 2022;Öztürk et al, 2020) As a result of the research, it was found that there was a significant positive relationship between the empowering leadership characteristics of school principals according to the perceptions of teachers and the psychological ownership levels of teachers and that the empowering leadership characteristics of school principals affected the psychological ownership levels of teachers. It is thought that the delegation of authority transferred to the employee with the effect of empowering leadership, giving responsibility to the employee, and providing guidance in the work to be done cause the employee to own the institution psychologically.…”
Section: Discussionmentioning
confidence: 99%
“…There is empirical evidence in the literature revealing that career satisfaction is a variable that influences work engagement. According to Gunes (2022), there is a positive correlation between career satisfaction and the work engagement variable. The employee will be more emotionally attached to his organization when he thinks that he is offered the opportunity to develop mentally and that his development is supported by challenging tasks (Carleton, 2011).…”
Section: Career Satisfaction and Work Engagement Relationshipmentioning
confidence: 99%